On the constitutive equation of AA2017 aluminium alloy at high temperature. (October 2016) - Giuliano, G.
Abstract: This study describes an original procedure to define the material constants present in the constitutive equation for the aluminium alloy Al 2017. Free bulging forming tests were therefore carried out using pressurised gas and an inverse analysis technique was applied based on minimising the difference between the data obtained from experimental activity and the data that can be obtained from numerical simulation carried out using the finite element method. The free bulging forming tests under pressure were carried out at a constant temperature (sheet metal temperature T = 438 °C) and using circular sheets characterised by an initial thickness of 0.55 mm. The constants of the material obtained by means of the proposed procedure allowed a free bulging forming process under pressure to be simulated in order to produce an axisymmetric tray. The results of a comparison between the numerical simulation and the experimental activity corresponded well and this showed that the material constants are reliable.